2017
DOI: 10.1159/000464337
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Phyto-Derived Ceramides in Improving Epidermal Barrier Function

Abstract: The outer most layer of the skin, the stratum corneum, consists of corneocytes which are coated by a cornified envelope and embedded in a lipid matrix of ordered lamellar structure. It is responsible for the skin barrier function. Ceramides (CERs) are the backbone of the intercellular lipid membranes. Skin diseases such as atopic dermatitis and psoriasis and aged skin are characterized by dysfunctional skin barrier and dryness which are associated with reduced levels of CERs. Previously, the effectiveness of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 158 publications
(294 reference statements)
1
51
1
2
Order By: Relevance
“…It should be noted that some popular over-the-counter moisturizers also include a skin-identical or synthetic ceramide, or pseudoceramide [7]. Although these ceramides, if provided at sufficient concentrations, can improve epidermal permeability barrier and SC hydration [8], their content in most formulations is usually too low to impart measurable benefits.…”
Section: Moisturizers Do Not Equate With Barrier Repair Therapymentioning
confidence: 99%
“…It should be noted that some popular over-the-counter moisturizers also include a skin-identical or synthetic ceramide, or pseudoceramide [7]. Although these ceramides, if provided at sufficient concentrations, can improve epidermal permeability barrier and SC hydration [8], their content in most formulations is usually too low to impart measurable benefits.…”
Section: Moisturizers Do Not Equate With Barrier Repair Therapymentioning
confidence: 99%
“…Keratinocytic lipid synthesis is mostly an autonomous process and produces not only cholesterol and cholesterol derivates but also free fatty acids (FFAs) with different chain lengths as well as triglycerides [14]. Additionally, ceramides (CERs) are synthesised in the endoplasmic reticulum of the keratinocytes, and their anisometric molecular structure differs markedly from other lipid classes [15,16]. Due to load differences within their long-chain molecules, CERs are able to spontaneously form lyotropic mesophases (also known as liquid-crystalline membrane structures) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise roles of pro-inflammatory leukotrienes [32] and anti-inflammatory lipoxins/resolvins [33, 34] in atopic diseases are not completely understood. A recent study reported that patients suffering from atopic dermatitis show an altered profile of lipids in blood plasma [35] and in the skin [36] and these data have been suggested to point towards an increased production of ALOX-derived pro-inflammatory mediator [35]. IL-4 has previously been identified as regulator of the ALOX pathway in monocytes/macrophages and dendritic cells [21, 22, 37], and microarray-based expression profiles suggested that IL-4 strongly upregulates the expression of ALOX15 and ALOX15B [21, 22, 37, 38].…”
Section: Discussionmentioning
confidence: 99%